Knowledge, attitude and practice (KAP) regarding folate intake among female students in International Islamic University Malaysia (IIUM) Kuantan - Tajuddin, Nur Afifah; Ahmad Yusof @ Hanafi, Hanani (Community Health Society Malaysia, 2020)
Background: Knowledge regarding folate intake plays important role in public health especially for women in the reproductive age, since lacking of folate intake may cause neural tube defects in baby during pregnancy. However, the level of knowledge regarding folate of women in the reproductive age in many parts of the world are of concern. The aim of this study was to examine the knowledge, attitude and practice of folate intake among female undergraduate students in International Islamic University Malaysia (IIUM) Kuantan campus. Besides that, this study also aims to assess the relationship between the KAP regarding folate among female IIUM Kuantan undergraduate students. Materials and Methods: This was a cross-sectional study whereby 111 female undergraduate students had completed an online survey questionnaire using Google Docs. The questionnaire consists of 71 questions which were divided into four parts (social-demographic characteristic, knowledge and attitude regarding folate and practice of folate intake). The data was analysed by descriptive frequency and Pearson correlation test to find the association between KAP of folate among female IIUM Kuantan undergraduate students. Result: Overall, 91% of the respondents ever heard about folate. All respondents have a very good attitude regarding folate however only 8% were assessed with good practice of folate intake. Significant correlation was observed between knowledge and attitude regarding folate but not for other factors. Conclusion: This study indicates that the respondents have a good knowledge and attitude towards folate intake, but not portrayed in their daily practice. This could be due to their marital status where all of them are single, still in study period and yet to pregnant, thus folate intake is not necessary at the current time.